Analysis of the Influence of Job Demand, Task Repetitiveness, and Role Ambiguity on Employee Boredom in Startup Companies - Sri Purwati; Susanto; Sofia Maulida; Roy Setiawan; Sonya Sidjabat; Mohammad Azharie Hamdany (Journal of Innovative and Creativity, 2025)
This study aims to explore how job demand, task repetitiveness, and role ambiguity influence employee boredom among Generation Z employees in startups in Indonesia. Using a quantitative approach, data were collected through a survey of 150 purposively selected respondents. Respondent criteria included Generation Z employees who had worked for at least one year and held staff positions in startups operating in five major cities in Indonesia. Data collection was conducted using a questionnaire with a five-point Likert scale, and analysis was conducted through multiple linear regression. The results show that collectively, job demand, task repetitiveness, and role ambiguity have a significant influence on employee boredom. Individually, all three variables also show a positive influence, meaning that the higher the job demands, the more frequently tasks are repeated, and the more unclear the employee's role, the greater the likelihood of boredom at work. These findings contribute to the organizational behavior literature and provide practical recommendations for startup management to develop more effective human resource management strategies, such as balancing workloads, creating variety in tasks, and clarifying each employee's role to reduce the risk of boredom and increase overall team productivity.